2018
DOI: 10.1186/s12951-018-0379-5
|View full text |Cite
|
Sign up to set email alerts
|

Food-grade TiO2 is trapped by intestinal mucus in vitro but does not impair mucin O-glycosylation and short-chain fatty acid synthesis in vivo: implications for gut barrier protection

Abstract: BackgroundTitanium dioxide (TiO2) particles are commonly used as a food additive (E171 in the EU) for its whitening and opacifying properties. However, the risk of gut barrier disruption is an increasing concern because of the presence of a nano-sized fraction. Food-grade E171 may interact with mucus, a gut barrier protagonist still poorly explored in food nanotoxicology. To test this hypothesis, a comprehensive approach was performed to evaluate in vitro and in vivo interactions between TiO2 and intestinal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 74 publications
1
39
0
1
Order By: Relevance
“…The E171 sample was obtained from a French commercial supplier of food coloring. The TiO 2 particle suspensions (> 95% anatase, [6]) were prepared in milliQ water following the generic Nanogenotox dispersion protocol [44], and the physicochemical properties of the particles in the E171 batch have been characterized in previous studies [6,7,45].…”
Section: Particle Preparationmentioning
confidence: 99%
“…The E171 sample was obtained from a French commercial supplier of food coloring. The TiO 2 particle suspensions (> 95% anatase, [6]) were prepared in milliQ water following the generic Nanogenotox dispersion protocol [44], and the physicochemical properties of the particles in the E171 batch have been characterized in previous studies [6,7,45].…”
Section: Particle Preparationmentioning
confidence: 99%
“…On top of HT29-MTX cells, TiO 2 particles would be trapped in mucus islands. 28 Conversely, on top of Caco-2 cells, which are not protected by mucus, agglomerates of TiO 2 can cause damage to epithelial cells, including disruption of the brush border, because of the mass of TiO 2 that settles down on the microvilli, 63 but also because of the movement of TiO 2 agglomerates in the vicinity of the microvilli, as previously demonstrated. 4 This bias could be avoided by using inverted cultures or microgravity reactors.…”
Section: Discussionmentioning
confidence: 81%
“…13 However, Talbot et al recently showed that the sub-chronic oral exposure of rats to E171 had little or no impact on the quantity and quality of intestinal mucus, and concluded that the protective function of mucus remained intact. 28 Therefore, this suggests that the reduced number of goblet cells reported by Urrutia-Ortega et al would have a limited physiological consequence for healthy persons.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations